2000
DOI: 10.1021/jp000732d
|View full text |Cite
|
Sign up to set email alerts
|

Extensive ab Initio Study of the C2O2, C2S2, and C2OS Systems: Stabilities and Singlet−Triplet Energy Gaps

Abstract: Ab initio molecular orbital theory has been used to study the three lowest open shell states of ethylenedione, C 2 O 2 , 2-thiooxoethen-1-one, C 2 OS, and ethylenedithione, C 2 S 2 . To treat the singlet and triplet states in an even-handed manner, multiconfigurational self-consistent field theory (MCSCF), which included all the important configurations for a quantitative description of these states, was used as the basis of the investigation. Further correlation effects have been included using a multireferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 59 publications
1
41
0
Order By: Relevance
“…[7,10,11,19] Ther elevant states involve two nearly degenerate orbitals,6 b u and 2a u (at a C 2h geometry), which are shown schematically in Figure 2A.A t linearity,they turn into the degenerate 2p u orbitals,and their population with two electrons gives rise to the 3 S g À , 1 D g ,a nd 1 S g + states of OCCO,a si ndicated in Figure 2B (right). The energy gaps shown are from the MRCI/cc-pVTZ//B3LYP/6-311 + G(2df) calculations by Talbi and Chandler.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…[7,10,11,19] Ther elevant states involve two nearly degenerate orbitals,6 b u and 2a u (at a C 2h geometry), which are shown schematically in Figure 2A.A t linearity,they turn into the degenerate 2p u orbitals,and their population with two electrons gives rise to the 3 S g À , 1 D g ,a nd 1 S g + states of OCCO,a si ndicated in Figure 2B (right). The energy gaps shown are from the MRCI/cc-pVTZ//B3LYP/6-311 + G(2df) calculations by Talbi and Chandler.…”
mentioning
confidence: 92%
“…Theaverage spacing of 417(15) cm À1 is close to the 396 cm À1 frequency of the trans-bending mode of 3 S g À OCCO,a sp redicted by MCSCF/cc-pVTZ calculations. [10] TheS 1 pedestal extends lower in energy than the triplet EA value owing to the dissociative nature of the singlet. Thea diabatic minimum of the singlet surface corresponds to the CO( 1 S + ) + CO( 1 S + ) limit, some 2.55 eV below the triplet equilibrium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown by recent sophisticated calculations (MCSCF, MRCI), among other points [44], that the singlet state of C 2 S 2 lies below the ground-state of the dissociation Scheme 2 product. Mass spectrometrical and theoretical studies have contributed significantly to the understanding of this area [45].…”
mentioning
confidence: 99%
“…The linear negative ion SCCS Ϫ is the most plausible candidate of the spectral carrier, since the species has two equivalent carbon atoms, for which the rotational constant is estimated to be about 0.05 cm Ϫ1 . Several theoretical works 23,26,27,29 have shown that the neutral species SCCS has the 3 ⌺ g Ϫ ground electronic state corresponding to the electronic configuration ...(7 g ) 2 (2 u ) 4 (2 g ) 4 (3 u ) 2 . When one electron is removed to form the positive ion SCCS ϩ , the ground electronic configuration should be ...(7 g ) 2 (2 u ) 4 (2 g ) 4 (3 u ) 1 , leading to the X 2 ⌸ u ͑regular͒ electronic state.…”
Section: Speciesmentioning
confidence: 99%